2021
DOI: 10.3390/v13040603
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Infectious Sindbis Virus by Yeast Spheroplast-Mammalian Cell Fusion

Abstract: Sindbis virus (SINV), a positive-sense single stranded RNA virus that causes mild symptoms in humans, is transmitted by mosquito bites. SINV reverse genetics have many implications, not only in understanding alphavirus transmission, replication cycle, and virus-host interactions, but also in biotechnology and biomedical applications. The rescue of SINV infectious particles is usually achieved by transfecting susceptible cells (BHK-21) with SINV-infectious mRNA genomes generated from cDNA constructed via in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Standard recombinant DNA methods were used. The details are found in the Supplementary Methods document. …”
Section: Methodsmentioning
confidence: 99%
“…Standard recombinant DNA methods were used. The details are found in the Supplementary Methods document. …”
Section: Methodsmentioning
confidence: 99%
“…Other promising genome engineering approaches include retron-associated recombineering, which uses the bacterial retron reverse transcriptase to continuously produce mutagenic oligos in vivo ( Lopez et al, 2022 ; Schubert et al, 2021 ), as well as synthetic base editing enzymes ( Gaudelli et al, 2017 ; Komor et al, 2016 ; Mok et al, 2020 ) and prime-editing enzymes ( Anzalone et al, 2019 ). I am also excited by the recent work of Ding, et al, who showed that yeast harboring a Sindbis virus cDNA driven by the strong, galactose-inducible Gal1 promoter can produce infectious transcripts and initiate replication upon fusion of the induced yeast with mammalian cells, thereby avoiding the need to isolate a cDNA and transcribe RNA in vitro ( Ding et al, 2021 ). I imagine a nearby future whereby nearly all standard molecular virology may be outsourced to yeast: we will be able to program yeast to create mutants of interest, such as with eMAGE, and to then produce infectious RNAs by feeding them galactose ( Fig.…”
Section: Novel Methods and Future Directionsmentioning
confidence: 99%
“…Reverse genetics is a conventional method for studying the pathogenesis and virulence of viruses ( Hao et al., 2021 ; Ding et al., 2021 ). Recently, complementary DNA (cDNA) clones of CV-B3, CV-A10, CV-A6, CV-A16, EV-A71, and EV-D68 have been constructed, and the biological characteristics of the rescued viruses have been validated ( Liu et al., 2019 ; Ma et al., 2015 ; Yang et al., 2015 ; Pan et al., 2018 ; Wang et al., 2020 ).…”
mentioning
confidence: 99%